Modification, processing, and subcellular localization in Escherichia coli of the pCloDF13-encoded bacteriocin release protein fused to the mature portion of beta-lactamase. - Luirink, J (1987)
A fusion between the pCloDF13-derived bacteriocin release protein and beta-lactamase was constructed to investigate the subcellular localization and posttranslational modification of the bacteriocin release protein in Escherichia coli. The signal sequence and 25 of the 28 amino acid residues of the mature bacteriocin release protein were fused to the mature portion of beta-lactamase. The hybrid protein (Mr, 31,588) was expressed in minicells and whole cells and possessed full beta-lactamase activity. Immunoblotting of subcellular fractions revealed that the hybrid protein is present in both the cytoplasmic and outer membranes of E. coli. Radioactive labeling experiments in the presence or absence of globomycin showed that the hybrid protein is modified with a diglyceride and fatty acids and is processed by signal peptidase II, as is the murein lipoprotein. The results indicated that the pCloDF13-encoded bacteriocin release protein is a lipoprotein which is associated with both membranes of E. coli cells.